Separation and purification of biomacromolecules based on microfluidics. Issue 14 (31st March 2020) - Vicente, Filipa A.; Plazl, Igor; Ventura, Sónia P. M.; Žnidaršič-Plazl, Polona
Abstract : Separation and purification of biomacromolecules either in biopharmaceuticals and fine chemicals manufacturing, or in diagnostics and biological characterization, can substantially benefit from application of microfluidic devices. Abstract : Separation and purification of biomacromolecules either in biopharmaceuticals and fine chemicals manufacturing, or in diagnostics and biological characterization, can substantially benefit from application of microfluidic devices. Small volumes of equipment, very efficient mass and heat transfer together with high process control result in process intensification, high throughputs, low energy consumption and reduced waste production as compared to conventional processing. This review highlights microfluidics-based separation and purification of proteins and nucleic acids with the focus on liquid–liquid extractions, particularly with biocompatible aqueous two-phase systems, which represent a cost-effective and green alternative. A variety of microflow set-ups are shown to enable sustainable and efficient isolation of target biomolecules both for preparative, as well as for analytical purposes.